17th AIAA/CEAS Aeroacoustics Conference (32nd AIAA Aeroacoustics Conference) 2011
DOI: 10.2514/6.2011-2821
|View full text |Cite
|
Sign up to set email alerts
|

Computational and Experimental Study on Noise Generation from Tire-Axle Regions of a Two-Wheel Main Landing Gear

Abstract: The purpose of this paper is computational and experimental investigation of flowfield related to noise generation mechanism from tire-axle regions of a two-wheel main landing gear. Flowfield around tire-axle is complicated with the existence of complicated geometries such as torque link, brake-caliper, and wheel cap. The unsteady flowfields around tire-axle are investigated with change of the torque link setting by unsteady CFD computations on the detail geometry. Three configurations; (1) baseline configurat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 29 publications
1
11
0
Order By: Relevance
“…The present results are in consistence with the experimental ones. Overall, it is comparably good with the one from the up-wind scheme but B-spline [10] Upwind [20] Fig. 7 Ensemble averaged streamwise velocities at y = 0.…”
Section: Turbulent Flow Around a Circular Cylinder Atsupporting
confidence: 53%
See 1 more Smart Citation
“…The present results are in consistence with the experimental ones. Overall, it is comparably good with the one from the up-wind scheme but B-spline [10] Upwind [20] Fig. 7 Ensemble averaged streamwise velocities at y = 0.…”
Section: Turbulent Flow Around a Circular Cylinder Atsupporting
confidence: 53%
“…These flow properties require very fine meshes and the low-dissipation numerical schemes in LES, since the location of the transition point is very sensitive to numerical dissipation. Large numerical dis-sipations could delay the transitions and increase the lengths of laminar shear layers [10]. The noise calculations raise two more challenges: the broadband dipole noise generated by pressure fluctuations on the cylinder surfaces and the broadband quadrupole noise by turbulent wake structures.…”
Section: Introductionmentioning
confidence: 99%
“…They found the largest contribution of the torque arm to the noise level and difference of SPL in the mid-and high-frequency range between fully-dressed and partially-dressed configurations. JAXA has conducted research work on noise generation mechanism and reduction technologies about two-wheel landing gears since 2008 [9][10][11][12][13] . The research model geometry is based on the current two-wheel landing gears design for regional jets.…”
Section: Introductionmentioning
confidence: 99%
“…Although, the NLG geometry is not as detailed as a realistic landing gear, the present case is geometrically complex when compared to previous configurations which were utilized to study cavity flow 15 . A number of previous studies involving simulation of complex NLG were found in the literature [16][17][18][19][20][21][22][23] . However, in those studies, cavity flow associated with the NLG was not considered.…”
Section: Test Configurationmentioning
confidence: 99%